2001
DOI: 10.1212/wnl.56.4.442
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in ALS is maintained as physical function declines

Abstract: QOL in patients with ALS appears to be independent of physical function, which agrees with a previous cross-sectional study. The ALS-specific health-related QOL score is primarily a measure of physical function. QOL instruments that assess spiritual, religious, and psychological factors produce different results than those obtained using measures of physical function alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
121
5
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(147 citation statements)
references
References 22 publications
10
121
5
7
Order By: Relevance
“…This also applies if the persons suffering from neuromuscular diseases and having a higher degree of education degree of education report on the general overall quality of life. In contrast to the findings of Robbins et al (2001), Lulé et al (2008), and Raspe (1990), the assessment of overall quality of life within the scope of this survey of persons having a neuromuscular disease is lower than in a comparison sample with persons not suffering from neuromuscular or other chronic diseases.…”
Section: Resultscontrasting
confidence: 91%
See 1 more Smart Citation
“…This also applies if the persons suffering from neuromuscular diseases and having a higher degree of education degree of education report on the general overall quality of life. In contrast to the findings of Robbins et al (2001), Lulé et al (2008), and Raspe (1990), the assessment of overall quality of life within the scope of this survey of persons having a neuromuscular disease is lower than in a comparison sample with persons not suffering from neuromuscular or other chronic diseases.…”
Section: Resultscontrasting
confidence: 91%
“…It means that difficult living conditions do not necessarily have to result in poorer assessments of subjective well-being or quality of life (Daig & Lehmann, 2007). Robbins et al (2001) showed that the assessment of the quality of life of patients with ALS does not primarily depend on the physical state of health. In a study by Lulé et al (2008), the average subjective quality of life of ALS patients was 66-72 % and thus in an area that is comparable with healthy control persons.…”
Section: Quality Of Life Within the Framework Of Neuromuscular Diseasesmentioning
confidence: 99%
“…In our study, most patients had moderate to high grade lymphedema and just a few low grade patients with lymphedema were present to be evaluated. PF improvement in the present study, as other studies showed (24,25) is not significantly related to HRQoL. So improvement in PF and HRQOL after treatment of lymphedema must be evaluated from different aspects (11).…”
Section: Discussionsupporting
confidence: 45%
“…The primary outcome measure was slope of the ALSFRS-R. Secondary measures consisted of changes in FVC slope, weight loss, the single-item ALS Quality of Life Scale, 15 and time to failure (defined as death, endotracheal intubation, tracheostomy-assisted ventilation, or use of noninvasive ventilation 23 hours/day for 14 days). Safety was assessed by adverse events and abnormal laboratory studies.…”
Section: Procedures Als Functional Rating Scale-revisedmentioning
confidence: 99%